2018
DOI: 10.1088/2040-8986/aaadc7
|View full text |Cite
|
Sign up to set email alerts
|

Strong coupling of collection of emitters on hyperbolic meta-material

Abstract: Recently considerable effort is devoted to the realization of the strong coupling regime of the radiation matter interaction in the context of emitter at a meta surface. The strong interaction is well realized in cavity quantum electrodynamics which also shows that the strong coupling is much easier to realize using a collection of emitters. Keeping this in mind we study if emitters on a hyperbolic meta materials can yield strong coupling regime. We show that the strong coupling can be realized for densities o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…4,5 It has also been demonstrated that a collection of emitters on hyperbolic materials show strong coupling. 6 Modification of spontaneous emission rate of dye molecules, 7 rare earth ions 8 and strong coupling of semiconductor quantum dots 9 in vicinity of HMM is reported. The transition energy can be tuned by changing the fabrication parameters.…”
Section: Introductionmentioning
confidence: 94%
“…4,5 It has also been demonstrated that a collection of emitters on hyperbolic materials show strong coupling. 6 Modification of spontaneous emission rate of dye molecules, 7 rare earth ions 8 and strong coupling of semiconductor quantum dots 9 in vicinity of HMM is reported. The transition energy can be tuned by changing the fabrication parameters.…”
Section: Introductionmentioning
confidence: 94%
“…* kallurureddy@iisc.ac.in It has been demonstrated that a collection of emitters on hyperbolic materials show strong coupling near the OTT set-in point [11]. Modification of spontaneous emission rate of dye molecules, [12] rare earth ions [13], and strong coupling of semiconductor quantum dots [14] in the vicinity of HMM is reported.…”
Section: Introductionmentioning
confidence: 96%
“…21,27−32 been demonstrated. 32 However, strong coupling has yet to be demonstrated between the bulk large wavevector modes, the VPPs, in an HMM and an embedded emitter or absorber. Previous theoretical work demonstrated that it should be possible to strongly couple a VPP mode and the intersubband transition (ISBT) of a quantum well (QW) in a layered semiconductor HMM system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Strong coupling was first demonstrated with a single Rydberg atom in a microwave cavity, and strong coupling to a single emitter has remained an important area of focus since it opens new possibilities for studying a variety of light–matter interactions, like single atom lasing , and quantum entanglement . Since the first experimental demonstration, strong coupling has been demonstrated in a variety of systems, primarily focusing on emitters located near metamaterials or within microcavities and photonic crystals. , Strong coupling of quantum dot emitters near an HMM has also been demonstrated . However, strong coupling has yet to be demonstrated between the bulk large wavevector modes, the VPPs, in an HMM and an embedded emitter or absorber.…”
Section: Introductionmentioning
confidence: 99%